Antiepileptic activity and potential mechanism of full-spectrum hemp extract - Zengliang Jin; Zhuo Huang (Fundamental Research)
Epilepsy is the fourth most common neuropsychiatric disorder. Although the approval of Epidiolex has ignited hope for patients, there is still a large gap in the field of anti-seizure research. The effect and underlying mechanism of full-spectrum hemp extract (HE) remains unclear. Here this study investigated the anti-seizure effect of HE on seizure models. The results showed that HE significantly reduced seizure susceptibility and prolonged seizure latency with better pharmacokinetic performance compared to CBD. This article then further explored the anti-seizure active components and their possible mechanism in HE. The results indicated that cannabichromene (CBC) and cannabinol (CBN) were involved in the anti-seizure process, especially CBC showed a strong allosteric enhancement effects on CBD binding site of the GABAA receptor, which implied that the GABAA receptor seemed to be the primary anti-epileptic target of HE. This article not only presents the great potential of HE as a candidate for new anti-epileptic drugs with less psychoactive, but also provides a valuable contribution to subsequent mechanism research and drug development on epilepsy.Abstract: Epilepsy is the fourth most coneuropsychiatric disorder. Although the approval of Epidiolex has ignited hope for patients, there is still a large gap in the field of anti-seizure research. The effect and underlying mechanism of full-spectrum hemp extract remains unclear. Here this study investigated the anti-seizure effect of HE on seizure models. The results showed that HE significantly reduced seizure susceptibility and prolonged seizure latency with better pharmacokinetic performance compared to CBD. This article then further explored the anti-seizure active components and their possible mechanism in HE. The results indicated that cannabichromene and cannabinol were involved in the anti-seizure process, especially CBC showed a strong allosteric enhancement effects on CBD binding site of the GABAA receptor, which implied that the GABAA receptor seemed to be the primary anti-epileptic target of HE. This article not only presents the great potential of HE as a candidate for new anti-epileptic drugs with less psychoactive, but also provides a valuable contribution to subsequent mechanism research and drug development on epilepsy.